Gender Stereotypes in Moana (2016): A Film Analysis of The Main Character - Yogi Zanualdy Ramadhan (Universitas Pendidikan Indonesia (UPI), 2019)
Gender stereotyping is a common phenomenon shown in films. Many films, such as those produced by Disney, often portray their male and female characters stereotypically. One of Disney’s recent children movies is Moana (2016). This research aims to analyze how the main character in Moana (2016) is portrayed and seeks to answer whether the portrayal conform to or goes against gender stereotypes. To analyze the gender stereotypes embedded in the film, the study draws on Evans and Davies’ (2009) framework as well as those of Copenhaver’s (2002) and Brannon’s (2016). Meanwhile, Boggs and Petrie’s (2008) characterization in films has been adopted to unravel the character of Moana. The analysis shows that Moana is portrayed as a character who possesses both masculine and feminine traits; the masculine traits, however, are more dominant that the feminine ones. This indicates that the film tends to go against gender stereotyping by portraying a complexity of traits within the main character. Keywords: Disney’s Movie, Gender Stereotypes.